A case study: the knowledge and awareness levels of copyright infringement among learners utilising digital technologies in Sunway College Johor Bahru - Krishnaveni Sritharan, *; Wee, Vivien Mui Eik *; Chin, Rachel May Ying; Jong, Emmy Ee Mei (Sunway College Kuala Lumpur, 2015)
Technologies especially Web 2.0 tools and mobile devices are transforming the way education is delivered. As such higher education institutions are experiencing an emerging pedagogical trend that may cause copyright infringement. The Copyright Act 1987 was legislated to inspire continuing creative work among academicians. Hence, the knowledge and awareness of Copyright Law and its infringement becomes increasingly significant in protecting the academicians’ work. Unawareness of the law can cause students to infringe the law and it can affect academicians’ work. An initial survey was conducted on 127 first year students from all nine programmes of Sunway College Johor Bahru. The results reveal that although the respondents have a relatively high awareness level and claim to understand the infringement; their actual knowledge level is only approximately 50% of the law. Also, the knowledge and awareness levels have very little correlation with the attitude level towards the Copyright Law.